A jaboticaba extract prevents prostatic damage associated with aging and high-fat diet intake. Issue 2 (31st January 2020) - Lamas, C. A.; Kido, L. A.; Montico, F.; Collares-Buzato, C. B.; Maróstica, M. R.; Cagnon, V. H. A.
Abstract : Jaboticaba extract prevented the prostatic lesion development in aging and/or overweight mice, mainly interfering in cell proliferation, hormonal and angiogenesis pathways. Abstract : Aging and overweight are involved in prostatic lesion development, due to their association with cell proliferation, hormonal imbalance and angiogenesis. The jaboticaba fruit is rich in bioactive compounds, showing potential chemopreventive action such as the capacity to modulate hormones and angiogenesis hallmarks. This study aimed to evaluate the jaboticaba extract (PJE) effect on the prostate morphology and on molecules related to hormone signaling and angiogenesis, during aging and/or high-fat diet (HFD) intake. Seventy FVB mice were distributed into experimental groups: YG group (young: 3 month old mice), AG group (aged: 11 month old mice), HfAG group (aged + HFD), JAGI group (aged + 2.9 g kg −1 PJE), JAGII group (aged + 5.8 g kg −1 PJE), HfJAGI group (aged + HFD + 2.9 g kg −1 PJE) and HfJAGII group (aged + HFD + 5.8 g kg −1 PJE). The ventral prostate was collected for morphological, immunohistochemistry and western-blotting analysis after 60 days of treatment. All PJE treatments promoted hormonal signaling balance and inhibited angiogenesis in the prostates of aged or HFD-fed aged mice, leading to the maintenance of healthy prostate morphology. A high dose of the PJE (JAGII and HfJAGII groups) led to the best capacity to reduce AR (58.40% and 74.42%; p = 0.0240 and p = 0.0023), ERα (30.29% and 45.12%; p = 0.0004 and p < 0.0001), aromatase (39.54% and 55.94%; p = 0.0038 and p = 0.0020), and VEGF (50.81% and 67.68%; p < 0.0001) and increase endostatin immunoexpression. Moreover, HFD intake intensified the hormonal and angiogenic alterations in the aged mouse prostates, contributing to the increase in premalignant lesion incidence. The PJE exerted a dose-dependent positive effect on aged or HFD-fed aged mouse prostates, contributing to the gland microenvironment recovery, mainly due to the hormonal and angiogenic balance. Therefore, we suggest that the PJE can be a potential candidate for prostatic lesion prevention.